Pengaruh Nicholas Saputra sebagai Brand Ambassador terhadap Minat Beli Kanzler Crispy Chicken Nugget - Rafeby Zhenda Violet; Oktaviana Purnamasari (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
The use of Brand Ambassadors is becoming increasingly popular in marketing strategies to influence customer behavior. This study aims to measure the role of Nicholas Saputra as a brand ambassador, consumer purchase intention for Kanzler Crispy Chicken Nugget, and the influence of the brand ambassador on purchase intention, focusing on followers of the Instagram account @temankanzler. Using brand ambassador and consumer behavior theories, this study involves two variables: Brand Ambassador (X), consisting of four dimensions (Popularity, Credibility, Attractiveness, Strength), and Purchase Intention (Y), which includes four dimensions (Transactional Intention, Referential Intention, Preferential Intention, Exploratory Intention). A quantitative method was applied through a survey of 71 respondents, analyzed using descriptive statistics and simple linear regression with SPSS. The results indicate that the mean perception of respondents for variables X and Y is 3.80 (agree). Validity and reliability tests confirm that all statement items are valid and reliable. Simple linear regression shows a positive and significant influence of the brand ambassador on purchase intention, with a determination coefficient (Adjusted R²) of 0.789, meaning that 78.9% of the variation in purchase intention is explained by the Brand Ambassador variable, while 21.1% is influenced by other factors.